2011
DOI: 10.1007/s10593-011-0735-y
|View full text |Cite
|
Sign up to set email alerts
|

N-substituted 2,5-di(2-thienyl)pyrroles: application, production, properties, and electrochemical polymerization (review)

Abstract: In this review methods for the synthesis of substituted 2,5-di(2-thienyl)pyrroles are described, and various aspects of their application are discussed. The main emphasis is on the electrochemical behavior of the compounds, the possibility of their electrochemical polymerization, and their use as monomers for the production of conducting polymers -components for molecular electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Several reviews on synthesis approaches and potential for tailordesigning the SNS structures are available. 3,23,24 The synthesis of DTP derivatives was derived from the attempt to insert a bridging unit between adjacent thiophene rings in order to add structural material and enforce planarity improving electron delocalization. 25 One of the first heteroatom-bridged molecules investigated was dithieno[3,2-b:2′,3′-d]thiophene (DTT), 26 yet its functionalization was limited, thus its analog, dithieno[3,2-b:2′,3′-d] pyrrole (DTP) became of interest.…”
Section: The Novelty/significance Of Thiophene-pyrrole Hybrid Structuresmentioning
confidence: 99%
“…Several reviews on synthesis approaches and potential for tailordesigning the SNS structures are available. 3,23,24 The synthesis of DTP derivatives was derived from the attempt to insert a bridging unit between adjacent thiophene rings in order to add structural material and enforce planarity improving electron delocalization. 25 One of the first heteroatom-bridged molecules investigated was dithieno[3,2-b:2′,3′-d]thiophene (DTT), 26 yet its functionalization was limited, thus its analog, dithieno[3,2-b:2′,3′-d] pyrrole (DTP) became of interest.…”
Section: The Novelty/significance Of Thiophene-pyrrole Hybrid Structuresmentioning
confidence: 99%
“…Many investigators have demonstrated that covalent functionalization of conducting polymers could be obtained by synthesis of functionalized monomers bearing a prosthetic group, which are subsequently polymerised. 5 The progress of such systems strongly depends on efficient protein immobilization on polymer substrates. In order to reach this complex heterogeneous interaction the polymer surface must be functionalized with chemical groups that are reactive towards proteins in a way that surface functional groups (such as carboxyl, -COOH; amine, -NH 2 ; and hydroxyl, -OH) chemically or physically anchor the proteins to the polymer platform.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Plenty of the primordial glucose biosensors were established on H 2 O 2 produced in the enzymatic oxidation of glucose by glucose oxidase (GOx) or amperometric determination of consumed oxygen. 5 Electrochemical amperometric biosensors are widely used class of glucose biosensing. 28,29 Fabrications of amperometric biosensors are rely on the electroactivity of the substrate or the product of the enzymatic reaction (rst generation biosensors).…”
Section: Introductionmentioning
confidence: 99%
“…These two points creates interesting trend in reactivity difference of a-position of thiophene and b-position of pyrrole in the S E Ar reactions. 5 Development of new processing technique to obtain the polymer with a higher degree of order has immense importance for device performance. Conjugated polymers can be directly obtained in solid state from a soluble and structurally preorganized crystalline monomer by solid-state polymerization (SSP).…”
Section: Introductionmentioning
confidence: 99%